2017
DOI: 10.1155/2017/2675897
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Pyrophosphate for Removal of Trivalent Heavy Metals and Actinides Simulated by Retention of Europium

Abstract: This work addresses the synthesis of titanium pyrophosphate, as well as the characterization and evaluation of the sorption process of europium, for removal of trivalent heavy metals and actinides simulate. The evaluation of the surface properties of titanium pyrophosphate was carried out determining the surface roughness and surface acidity constants. The values obtained from the determination of the surface roughness of the synthesized solid indicate that the surface of the material presents itself as slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…is behavior could be related to the increase in porosity caused by irradiation of tausonite. is statement is supported by observations made by other authors, who have indicated that when the fit data respond to more than one line of fit, it is indicative that the sorption process is influenced by more than one diffusion phenomenon [13,40,41].…”
Section: Sorption Experimentssupporting
confidence: 80%
See 2 more Smart Citations
“…is behavior could be related to the increase in porosity caused by irradiation of tausonite. is statement is supported by observations made by other authors, who have indicated that when the fit data respond to more than one line of fit, it is indicative that the sorption process is influenced by more than one diffusion phenomenon [13,40,41].…”
Section: Sorption Experimentssupporting
confidence: 80%
“…Finally, the quantification of europium was performed by luminescence in a Jobin Yvon Horiba Fluorolog with a xenon lamp (450 W). 500 μL samples of the supernatant were excited at 397 nm and europium emission spectra were recorded from 570 nm to 650 nm and the highest peaks were quantified at 590 nm and 610 nm [13,19].…”
Section: Sorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation